Pemutusan Hubungan Kerja Bagi Karyawan Di Masa Pandemi Covid-19 Ditinjau Dari Perspektif Hukum Ekonomi Syariah - Faiz Nashrullah (Istinbath : Jurnal Hukum, 2021)
In the article, the focus of the discussion is on employee terminations that occur during a pandemic, and the things that companies must fulfill when terminating employment, in terms of Sharia Economic Law. The Covid-19 pandemic that hit caused the government to issue a policy to limit the movement of people by implementing a lockdown and/or PSBB policy. The program caused a stagnation of the wheels of the community's economy. Entrepreneurs suffer losses due to unstable economic conditions, and people's purchasing power has decreased drastically. Thus, to avoid greater losses, many companies cut production costs by terminating their employees. From the results of the study, it is known that termination of employment during the pandemic is included in the ijarah category which is in the company's department, which acts as musta'jir (tenant). In ijarah, musta'jir is allowed to terminate the employment relationship with strong reasons, for example, because of the threat of bankruptcy. The things that must be fulfilled by the company such as severance pay and long service awards are adjusted to the applicable law. If there is still a dispute, then the parties can use the islah agreement to find a middle way. So it can be concluded that termination of employment during a pandemic is something that is allowed according to sharia economic law, provided that the company's obligations to employees affected by the termination must be carried out, and if no agreement is reached between the company and employees regarding their respective rights and obligations. each party, then the parties can choose the islah method to find the best solution.